2021
DOI: 10.1029/2020jd033210
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Extreme Air Pollution Meteorology on Air Quality in China

Abstract: Extreme air pollution meteorological events (EAPMEs), such as atmospheric stagnation (AS), heat wave (HW), and temperature inversion, significantly affect regional air quality. In the present study, considerably increased EAPME frequency with clear spatial variations is identified in China from 1960 to 2019. Strong air quality sensitivities to EAPMEs are identified by combing air quality and meteorological observations. We found that HW greatly affects ozone concentration and may enhance the generation of fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 70 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have demonstrated that the formation of haze in Chinese megacities is associated with a complex interplay between emissions, transportation, meteorological conditions and atmospheric chemistry. [5][6][7][8][9][10][11][12][13][14] In Beijing, atmospheric new particle formation (NPF) tends to precede the formation of haze in winter. 5,15 The contribution of NPF and subsequent gas-to-particle conversion (GTP) associated with these newly formed particles to the increased PM 2.5 mass concentrations during the haze formation has, however, remained difficult to quantify.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the formation of haze in Chinese megacities is associated with a complex interplay between emissions, transportation, meteorological conditions and atmospheric chemistry. [5][6][7][8][9][10][11][12][13][14] In Beijing, atmospheric new particle formation (NPF) tends to precede the formation of haze in winter. 5,15 The contribution of NPF and subsequent gas-to-particle conversion (GTP) associated with these newly formed particles to the increased PM 2.5 mass concentrations during the haze formation has, however, remained difficult to quantify.…”
Section: Introductionmentioning
confidence: 99%
“…Daily mean PM 2.5 concentration and daily maximum 8-hr mean O 3 (hereafter "ozone8") from more than 367 cities and hourly PM 2.5 and O 3 concentration from more than 2000 observational sites in the period 2014-2020 were continuously collected from the China National Environmental Monitoring Center (shown in Figure 1a, (Yang & Shao, 2021)). Each city usually has 3-30 monitoring sites based on city size.…”
Section: Methodsmentioning
confidence: 99%
“…org.cn/en/zjljsjj_sm.html (Lu et al, 2021) [Dataset]). The air quality data from the China National Environmental Monitoring Centre are included in Yang and Shao (2021) and can be accessed from https://openaq.org/%23/countries. The global reanalysis data ERA5 are available in ECMWF at https://cds.climate.copernicus.eu/cdsapp#!/ (Hersbach et al, 2020) [Dataset].…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, the scientific research linked to human health and wellbeing of populations in urban and industrialized areas mainly focused on two issues: climate change and air quality [1][2][3][4][5][6][7][8][9][10]. Climate change affects human wellbeing through many related events: increased frequency and intensity of heat waves and cold waves, changing precipitation intensity, and increased devastating weather events, such as hurricanes, tornadoes, floods and droughts, cold-related mortality, and heat-related mortality [11][12][13][14][15][16][17]. Observed climate trends show that temperatures are increasing, particularly extreme temperatures, with heat waves (HWs) becoming more frequent, more intense, and longer lasting [3,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%